2012
DOI: 10.1007/s12291-012-0272-1
|View full text |Cite
|
Sign up to set email alerts
|

Unique Correlation Between Mutated Citrullinated Vimentine IgG Autoantibodies and Markers of Systemic Inflammation in Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) is the most common inflammatory systemic autoimmune disease, primarily affecting the peripheral joints. Anti-mutated citrullinated vimentin autoantibodies (anti-MCV) of IgG isotype were shown to be a useful diagnostic marker of RA especially in RA patients who were anti-cyclic citrullinated protein autoantibodies (anti-CCP) negative. Nevertheless, published data correlates rheumatoid factor (RF), anti-CCP or anti-MCV antibodies with either erythrocyte sedimentation rate (ESR) or serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…There were no significant differences in disease duration and Steinbrocker radiographic stage between anti‐Sa positive and anti‐Sa negative patients with RA. This may be explained by the reported association of the marker with disease activity at the time of obtaining the patient's blood sample . Surprisingly, there was no correlation between anti‐Sa and CRP or ESR in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in disease duration and Steinbrocker radiographic stage between anti‐Sa positive and anti‐Sa negative patients with RA. This may be explained by the reported association of the marker with disease activity at the time of obtaining the patient's blood sample . Surprisingly, there was no correlation between anti‐Sa and CRP or ESR in our study.…”
Section: Discussionmentioning
confidence: 99%
“…40% of RA RF (−) patients were found to have increased levels of these antibodies. Additionally, the presence of a-Sa was found to be positively correlated with ESR and CRP [27]. It is suggested that a-Sa level is a better indicator of radiographic progression risk than a-CCP level [28].…”
Section: Discussionmentioning
confidence: 91%
“…Rheumatoid arthritis (RA) is one of the most common autoimmune rheumatic disease of an ambiguous and complicated etiology characterized by a chronic, multisystemic and progressive inflammatory disorder affecting synovial joints (1,2), leading to functional capacity diminution, articular cartilage damage (3)(4)(5), deformity, disability and substantial economic costs (6)(7)(8)(9). The global prevalence of RA ranges between 0.5%-1% varies upon gender, population and ethnicity mostly in developing countries in young women and elderly people (3,5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the most common autoimmune rheumatic disease of an ambiguous and complicated etiology characterized by a chronic, multisystemic and progressive inflammatory disorder affecting synovial joints (1,2), leading to functional capacity diminution, articular cartilage damage (3)(4)(5), deformity, disability and substantial economic costs (6)(7)(8)(9). The global prevalence of RA ranges between 0.5%-1% varies upon gender, population and ethnicity mostly in developing countries in young women and elderly people (3,5,10). Above all, due to the aggressive nature and severity of the clinical manifestations of the disease process, also inaccuracy in the RA early diagnosis after symptoms onset, it is potentially recommended to differentiate between persistent RA and other forms of rheumatic diseases; while early diagnostics and prognostics approaches leads to prevent unwanted irreversible joint damages (8,11,12).…”
Section: Introductionmentioning
confidence: 99%